2007
DOI: 10.1152/jn.00988.2007
|View full text |Cite
|
Sign up to set email alerts
|

Task-Specific Depression of the Soleus H-Reflex After Cocontraction Training of Antagonistic Ankle Muscles

Abstract: Perez MA, Lundbye-Jensen J, Nielsen JB. Task-specific depression of the soleus H-reflex after cocontraction training of antagonistic ankle muscles. J Neurophysiol 98: 3677-3687, 2007. First published October 17, 2007 doi:10.1152/jn.00988.2007. Ballet dancers have small soleus (SOL) H-reflex amplitudes, which may be related to frequent use of cocontraction of antagonistic ankle muscles. Indeed, SOL H-reflexes are depressed during cocontraction compared with plantarflexion at matched background EMG level. We in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
73
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(76 citation statements)
references
References 48 publications
3
73
0
Order By: Relevance
“…The condition with low afferent gain implied an average reduction in the number of recruited motor neurons of 38.7% with respect to simulations with high gain. This corresponds well to the reduction in the H-reflex amplitude previously observed experimentally during cocontraction [approximated values: 10 -30% (Nielsen and Kagamihara 1993), 40 -60% (Nielsen and Kagamihara 1992), 40% (Perez et al 2007)]. In the antagonist (heteronymous) muscle, the Ia input generated a decrease in the baseline motor neuron activity (Fig.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…The condition with low afferent gain implied an average reduction in the number of recruited motor neurons of 38.7% with respect to simulations with high gain. This corresponds well to the reduction in the H-reflex amplitude previously observed experimentally during cocontraction [approximated values: 10 -30% (Nielsen and Kagamihara 1993), 40 -60% (Nielsen and Kagamihara 1992), 40% (Perez et al 2007)]. In the antagonist (heteronymous) muscle, the Ia input generated a decrease in the baseline motor neuron activity (Fig.…”
Section: Resultssupporting
confidence: 88%
“…This is reflected in the fact that even the background activity of stretch-sensitive muscle receptors contributes substantially to the neural drive to the muscles in steady, isometric contractions (Gandevia et al 1990;Macefield et al 1993). The functional relevance of both strategies is underlined by the fact that the level of cocontraction (Osu et al 2002;Shadmehr et al 1993) as well as the presynaptic inhibition of the Ia afferent input (Perez et al 2007;Roche et al 2011) are modulated during the process of learning a new motor task.…”
mentioning
confidence: 99%
“…A number of studies have demonstrated that the amplitude of reflex responses can change with practice Geertsen et al 2007;Perez et al 2007;Voigt et al 1998). For example, both healthy and spinal-cord injured subjects were able to decrease the amplitude of the stretch reflex in biceps brachii after 24 training sessions in which subjects were provided with feedback of the response and a reward for producing the desired adaptation (Segal and Wolf 1994;Wolf and Segal 1996).…”
Section: Change In Inhibitionmentioning
confidence: 99%
“…In addition to the attenuation of reflex inhibition from brachioradialis to biceps brachii, the increase in time to failure may have involved a reduction in recurrent inhibition, which declines during a sustained contraction (Löscher et al 1996), and an increase in excitatory input to biceps brachii motor neurons from afferents arising from forearm muscles (Cavallari and Katz 1989). In contrast, the adaptation likely did not involve a change in disynaptic reciprocal inhibition because the low level of EMG activity in triceps brachii did not change across the practice sessions (Perez et al 2007). These pathways are difficult to test in biceps brachii, however, due to the challenges associated with measuring the H reflex in this muscle (Klass et al 2008;Miller et al 1995a,b).…”
Section: Change In Inhibitionmentioning
confidence: 99%
See 1 more Smart Citation